2013
DOI: 10.1590/s2317-17822013000200016
|View full text |Cite
|
Sign up to set email alerts
|

Processamento temporal e consciência fonológica nas alterações de leitura e escrita: dados preliminares

Abstract: Keywordscrianças, entre 7 e 12 anos, com alterações de leitura e escrita confirmada após avaliação específica.Todos os participantes foram submetidos à avaliação da consciência fonológica, utilizando-se o teste de consciência fonológica -Instrumento de Avaliação Sequencial. Para avaliar o processamento auditivo temporal foram utilizados os testes de padrão de duração e frequência, realizados em cabina audiométrica.Resultados: A análise descritiva indicou desempenho alterado nas habilidades silábicas e fonêmica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…These correlations found in GI and GII suggest that auditory processing disorders may lead to a poor performance in phonological awareness skills in children with BECTS. This result corroborates with studies that have showed correlation between temporal auditory skills and phonological processing [ 51 , 54 ]. From these results, we believe that the temporal auditory processing deficits found in children of this sample could be related to difficulties in speech discrimination and phonological processing in this pediatric population, as previously reported in the literature [ 11 , 19 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These correlations found in GI and GII suggest that auditory processing disorders may lead to a poor performance in phonological awareness skills in children with BECTS. This result corroborates with studies that have showed correlation between temporal auditory skills and phonological processing [ 51 , 54 ]. From these results, we believe that the temporal auditory processing deficits found in children of this sample could be related to difficulties in speech discrimination and phonological processing in this pediatric population, as previously reported in the literature [ 11 , 19 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Specific deficits in perception and process of short acoustical elements and their order of occurrence have been associated in literature with impairments in language, reading, writing, and phonological processing [ 53 ]. According to Soares et al [ 54 ], difficulties to process stimuli that incorporate acoustic cues of short duration and sequence, as the speech is structured, may precede and predict subsequent disorders in phonological representation that have been found in children with impairments in language, reading, and writing.…”
Section: Discussionmentioning
confidence: 99%
“…Capellini, Germano e Cardoso (2008), verificaram em seus estudos que o baixo desempenho dos escolares com dislexia no teste dicótico de dígitos está relacionado a uma hipoperfusão do lobo temporal, e que este pode influenciar a percepção e sequencialização dos sons, impactando negativamente o processo de leitura desses escolares. Nos estudos de Soares et al (2013) os testes de processamento auditivo realizados em crianças com déficit de consciência fonológica, leitura e escrita apresentaram déficit nos aspectos temporais. De acordo com essa correlação, e considerando o déficit fonológico na dislexia, podemos relacionar os achados do autor com os achados do presente estudo.…”
Section: Discussionunclassified
“…Music training has been associated with better auditory temporal processing in several domains, including temporal resolution and sequencing, suggesting potential improvement specifically in the temporal sequencing domain [5,6,9]. Because temporal sequencing has been linked to improved language and reading abilities [9,22,23], the finding of improved sequencing outcomes following musical training in childhood holds important educational curriculum implications.…”
Section: Introductionmentioning
confidence: 99%